Curcuma longa rhizome extract and Curcumin reduce the adhesion of Acanthamoeba triangularis trophozoites and cysts in polystyrene plastic surface and contact lens. (December 2020) - Mitsuwan, Watcharapong; Sangkanu, Suthinee; Romyasamit, Chonticha; Kaewjai, Chalermpon; Jimoh, Tajudeen O.; de Lourdes Pereira, Maria; Siyadatpanah, Abolghasem; Kayesth, Sunil; Nawaz, Muhammad; Rahmatullah, Mohammed; Butler, Mark S.; Wilairatana, Polrat; et al.
Abstract: Curcuma longa and Curcumin have been documented to have a wide spectrum of pharmacological effects, including anti- Acanthamoeba activity. Hence, this study sought to explore the anti-adhesion activity of C. longa extract and Curcumin against Acanthamoeba triangularis trophozoites and cysts in plastic and contact lenses. Our results showed that C. longa extract and Curcumin significantly inhibited the adhesion of A. triangularis trophozoites and cysts to the plastic surface, as investigated by the crystal violet assay (P < 0.05). Also, an 80–90% decrease in adhesion of trophozoites and cysts to the plastic surface was detected following the treatment with C. longa extract and Curcumin at 1/2 × MIC, compared to the control. In the contact lens model, approximately 1 log cells/mL of the trophozoites and cysts was reduced when the cells were treated with Curcumin, when compared to the control. Pre-treatment of the plastic surface with Curcumin at 1/2-MIC reduced 60% and 90% of the adhesion of trophozoites and cysts, respectively. The reduction in 1 Log cells/mL of the adhesion of A. triangularis trophozoites was observed when lenses were pre-treated with both the extract and Curcumin. Base on the results obtained from this study, A. triangularis trophozoites treated with C. longa extract and Curcumin have lost strong acanthopodia, thorn-like projection pseudopodia observed by scanning electron microscope. This study also revealed the therapeutic potentials of C. longa extract and Curcumin, as such, have promising anti-adhesive potential that can be used in the management/prevention of A. triangularis adhesion to contact lenses. Graphical abstract: Image 1